2020
DOI: 10.3390/s20020563
|View full text |Cite
|
Sign up to set email alerts
|

Applying Fully Convolutional Architectures for Semantic Segmentation of a Single Tree Species in Urban Environment on High Resolution UAV Optical Imagery

Abstract: This study proposes and evaluates five deep fully convolutional networks (FCNs) for the semantic segmentation of a single tree species: SegNet, U-Net, FC-DenseNet, and two DeepLabv3+ variants. The performance of the FCN designs is evaluated experimentally in terms of classification accuracy and computational load. We also verify the benefits of fully connected conditional random fields (CRFs) as a post-processing step to improve the segmentation maps. The analysis is conducted on a set of images captured by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…This layer increases the resolution by replicating the values of the neighbors. To refine the spatial precision, FCN fuses the prediction layer with shallower layers of the network by summing predictions and applying a softmax function at the end (as shown in Figure 2a) (Long et al., 2015; Torres et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This layer increases the resolution by replicating the values of the neighbors. To refine the spatial precision, FCN fuses the prediction layer with shallower layers of the network by summing predictions and applying a softmax function at the end (as shown in Figure 2a) (Long et al., 2015; Torres et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The results confirmed that the original COVID-19 data could be well preprocessed to have comparable intensity distribution to that of well-curated normal data. F. Segmentation network analysis 1) Comparison with U-Net: Recall that we chose FC-DenseNet103 as a backbone segmentation network architecture thanks to its higher segmentation performance with smaller number of parameters (9.4 M) [31]. To demonstrate the effectiveness of CXR segmentation by the FC-Densenet103, we trained U-Net [32] under identical training conditions and compared the results.…”
Section: E Cross-database Generalization Capabilitymentioning
confidence: 99%
“…In [ 8 ] the authors showed that the fusion of Mask-Fast RCNN and OBIA methods increases by 25% the overall accuracy of the segmentation of scattered shrubs in UAV, airborne and GoogleEarth imagery. In [ 36 ] the authors evaluated the performance of five CNN-based methods for the semantic segmentation of a single endangered tree species, called Dipteryx alata Vogel, in UAV images. In particular, they evaluated SegNet, U-Net, FC-DenseNet, and two DeepLabv3+ variants and found that FC-DensNet overcomes all the previous methods with an overall accuracy of 96.7%.…”
Section: Related Workmentioning
confidence: 99%